Sophisticated technology innovation capability: entrepreneurial resilience on disaster - resilient MSMEs - Panjaitan, Roymon; Hasan, Muhammad; Vikaliana, Resista (Serbian Journal of Management, 2022)
The level of productivity should be increased and maintained to sustain the success of micro, small and medium enterprises (MSMEs). Furthermore, entrepreneurial resilience requires advanced technological innovation capabilities to avoid continual external disasters. Therefore, this research explores the connection between entrepreneurial resilience, disaster-resilient MSMEs, and new ideas on complex technical innovations to modulate entrepreneurship. Partial Least Squares are used to process 177 MSMEs respondents in Central Java, Indonesia and the findings successfully bridged the gap between entrepreneurial resilience and disaster-resistant MSMEs. The is mediated by sophisticated technology innovation capability. Furthermore, corporate owners and managers are concerned with the ongoing adaptation and creation of complicated technologies concerning sophisticated innovation capabilities. These findings indicate that entrepreneurial resilience contributes to sophisticated technological innovation capability. The findings also show that entrepreneurial resilience contributes to disaster-resilient MSMEs and demonstrate the importance of understanding how entrepreneurs survive during conditions of uncertainty. This theoretical conclusion gives rise to a new competitive resource advantage theory perspective in which sophisticated technology’s inventive capacities might be strengthened when entrepreneurial resilience is stronger. The entrepreneurial resilience can improve when corporate organizations or MSMEs players have advanced technical resource capabilities.
Keywords: Entrepreneurial Resilience; Sophisticated Technology Innovation Capability; Disaster-Resilient MSMEs